Pengaruh Tatakelola Dana Program Pemberdayaan Masyarakat Terhadap Akuntabilitas Program Pemerintahan Kota Kediri - Wiwiek Kusumaning Asmoro; Aang Afandi; Novie Astuti Setianingsih (Gorontalo Accounting Journal, 2020)
The purpose of this study was to analyze the Effect of Financial Governance of Community Empowerment Program Funds on Program Accountability. The research method used in this research is descriptive quantitative. The research shows the results of the influence of Prodamas' financial management on the level of program accountability in the villages of Pesantren District. Based on the results of the research, the variables of efficiency, economic effectiveness, access to information and reporting systems have achieved targets or goals for the benefit of residents who feel the benefits of the programs that have been implemented, and easy access to information and reporting systems in planning, implementing and reporting activities. So it can be concluded that the management of Prodamas funds at the Kelurahan level of the Kediri City Government Islamic Boarding School is good because it has been accountable for managing funds in the Community Empowerment Program.